Effective Mentoring in the Clinical Setting. (April 2016) - Shellenbarger, Teresa; Robb, Meigan
Abstract : This article is one in a series on the roles of adjunct clinical faculty and preceptors, who teach nursing students and new graduates to apply knowledge in clinical settings. This article describes mentoring strategies clinical instructors and preceptors can use to help ease novice nurses' transition to practice.